Study of musculoskeletal disorders in physical therapists: correlation with work routine. - Leal, Giselle Mirtes Amaral; Oliveira, Mafra Raiele Torres; Bastos, Vivianne Camila de Souza; Barros, Maria de Fátima Alcântara; Carvalho, Antônio Geraldo Cidrão de; Campos, Shirley Lima; Guerino, Marcelo Renato; Monte-Silva, Kátia Karina do; Tenório, Angélica da Silva; Araújo, Maria das Graças Rodrigues de (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Work-Related Musculoskeletal Disorders (MSDs) affect health professionals by frequent exposure to physical and mental overloads during the workday. Physiotherapy aims to promote functional health of the individual, however ergonomic conditions in their workplace are often precarious and associated with activities and repetitive movements resisted overload the musculoskeletal system inducing damage to your physical condition. Objective: To identify the occurrence of Musculoskeletal Disorders (DMEs) in physical therapists working in public and private health services in Recife-Pernambuco, recording determinants and establishing relationship with clinical practice and the workload of the tests. Method: Observational study of physiotherapists of both genders. Peres questionnaire were administered and collected personal information, professional performance and DMEs Results: Forty-one physiotherapists; 85.4% reported DMEs, females (80.5%); 41.4% between 24-30 years old; places of work, hospitals (70.7%) and clinical (63.4%); predominance of lesions in the spine and upper limbs; 65.7% changed work habits due to the occurrence of DMEs. Significant correlation between age and gender prevalence in females; since the occurrence of DMEs was not significantly correlated with time of practice, with workload, with the number of daily visits nor to rest at work. Conclusion: The volunteers showed high percentage of involvement by DMEs, especially in the spine, which seems to be related to the age and gender of the therapist. The study indicates that physical therapists are an exposed to risk for developing occupational musculoskeletal disorders profession, requiring awareness of students and professionals about proper use of the body itself, the risks of the profession in order to prevent future physical limitations.